E-Procurement Systems and Organizational Performance in Germany - Weber, Felix (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to analyze the e-procurement systems and organizational performance in Germany. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The implementation of e-procurement has streamlined procurement processes, reducing costs and improving efficiency through automation and better supplier management. Organizations adopting e-procurement systems report enhanced transparency, reduced procurement cycle times, and improved compliance with procurement regulations. Additionally, the data-driven nature of e-procurement allows for better decision-making and strategic sourcing, contributing to overall organizational effectiveness and competitiveness in the market. Unique Contribution to Theory, Practice and Policy: Technology acceptance model (TAM), resource-based view (RBV) & institutional theory may be used to anchor future studies on analyze the e-procurement systems and organizational performance in Germany. Establish regular and comprehensive training programs tailored to the needs of procurement staff to ensure effective utilization of e-procurement systems. Develop a national policy framework that encourages e-procurement adoption in both public and private sectors.